Spanish booksellers facing disruptive technological challenges - Magadán Díaz, Marta; Rivas García, Jesús Israel (Publishing Research Quarterly, 2020)
The present study focuses on the effects of technological change over the Spanish booksellers’ business models. For this purpose, it is conducted a survey amongst 103 Spanish bookstores belonging to the Spanish Confederation of Booksellers Associations. The results obtained from the statistical analysis have highlighted that the Spanish booksellers surveyed: (1) do not feel really threatened by e-books, (2) consider necessary both financial resources and technical qualification to develop the online distribution channel for bookselling, regardless of format, and (3) underline the barriers to the adoption of the e-book amongst their products are focused on the absence of a consolidated demand in their environment, the need for technical resources and the achievement of agreements with digital suppliers and publishers.
Keywords: Scopus; JCR